MO926: Development and Implementation of an Electronic Patient-Reported Outcome System to Support Health-Related Quality of Life Management in a Large, European Dialysis Network. (3rd May 2022) - Neri, Luca; Ion Titapiccolo, Jasmine; Goethel-Paal, Berit; Bellocchio, Francesco; Pizzo, Alessandro; Theodose, Maxime; Eva Baró Salvador, Maria; Schofield, Michaela; Cioffi, Mario; Rincon Bello, Abraham; Basnayake, Kolitha; Chrisholm, Chis; et al.
Abstract: BACKGROUND AND AIMS: Electronic patient-reported outcome measures (ePROMs) may help personalize healthcare for dialysis patients. ePROMs allow patients to self-report their symptoms and disease burden remotely and make the data available to healthcare professionals (HCP) in real-time. Such information can be used for digital phenotyping, symptoms and disease burden monitoring and to enable personalized healthcare through improved outcomes prediction, as well as Screen and Act, N-of-1 trials and treat-to-target approaches. However, routine use of ePROM in clinical practice presents several challenges, including respondent burden and a lack of clear guidance on medical and psycho-educational intervention in response to patients' complains. We sought to implement a quality improvement programme based on ePROM management in a large network of dialysis patients. METHOD: ePROM were collected as part of a screen and act programme launched for the first time in all centres belonging to the Fresenius Medical Care (FMC) Nephrocare network in France (FR), Italy (IT), Spain (SP), UK and Ireland (IR) starting on 20 September 2021. The screening phase ended on 4 December 2021. The action phase is still ongoing. The programme aims at screening all dialysis patients for undetected quality of life and adjustment problems and allow physicians, at their sole discretion, to provide remediation actions potentially including adjustment of treatment plan based on revision of patients' clinical charts and administration of health education modules. The questionnaire included KDQOL-36, the 5D-Itch questionnaire and an ad hoc module on intradialytic symptoms, and its content was mapped to SONG-HD initiative endpoints. ePROM were collected at the bedside or at patients' home with a web application available for tablet and smartphones either as self-report or assisted self-report. All ePROM data were recorded in EuCLiD®, the clinical information systems adopted by FMC Nephrocare clinics, as part of patients' clinical chart. A dashboard displaying patients' scores was shown to the attending healthcare professional upon survey completion. Statistics about patients' engagement, scores and action alerts are presented in clinical reports. In the present analysis, we report a retrospective analysis of data abstracted from the EuCliD® database. RESULTS: Overall, 152 centres (93%) joined the campaign. Participation statistics across countries are reported in Fig. 1. Among 11 537 active patients treated in the five participating countries, 1553 were ineligible because belonging to non-participating centres, temporarily transferred to other centres outside the network (i.e. vacation, rehabilitation, etc.), hospitalized, or because they were considered unable to respond to the survey (i.e. language barrier, inability to read and write or cognitive impairment). Around 23% (IT) to 30% (FR) were considered eligible with assisted administration only. Attrition rate ranged from 3% (IT) to 15% (FR). Item missingness was <2% for all items throughout the survey except for the item on sexual activity (>10% in all countries). KDQOL-36 scores are reported in Fig. 2; 22.5% reported moderate to very severe pruritus mostly distributed on the head/scalp, chest, abdomen, back, lower legs and thighs, forearm and upper arm (all >30% prevalence). Between 10% (IT) and 20% (UK) reported any complications during their last dialysis session, and between 6% (SP) and 12% (IR) suspended or interrupted treatment because of their symptoms. Prevalence of recovery time >3 h ranged from 34.8% (FR) to 46.4% (IR). CONCLUSION: The ePROM quality improvement campaign attained wide participation and low attrition. We found no evidence of respondent burden given the low missingness rate throughout the survey items. The screening phase allowed to collect and organize a wealth of patient-reported outcomes amenable of medical or psycho-educational interventions.